Brexit: A Loaded Narrative Told Through Metaphor Scenarios and Image Schemas - Martín de la Rosa, Victoria (Verbum, 2025)
This paper aims to analyze the discourse on Brexit produced by the pro-leave newspaper The Daily Telegraph in the run-up to the June 23, 2016, referendum, with the goal of understanding how this discourse was articulated, through metaphor scenarios and image schemas, to trigger anti-EU sentiment among its readers. The analysis was conducted across two scenarios: (a) what being part of the EU had meant up to that point, represented through three metaphorical scenarios—EU as a prison, EU as a moving vehicle, and EU as a nanny—all based on the blockage schema; and (b) what Brexit could mean instead, illustrated by the metaphors scenarios—Britain as a leader and Taking back control, both grounded in the enablement schema. Hence, the message communicated—delegitimizing the EU in the first scenario and legitimizing the desire of Great Britain to leave in the second—was further reinforced and naturalized through the coherence between metaphor scenarios and the sensory experience of image schemas.